Ibrutinib–rituximab followed by R-HCVAD as frontline treatment for young patients (≤65 years) with mantle cell lymphoma (WINDOW-1): a single-arm, phase 2 trial. Issue 3 (March 2022) - Wang, Michael L; Jain, Preetesh; Zhao, Shuangtao; Lee, Hun Ju; Nastoupil, Loretta; Fayad, Luis; Ok, Chi Young; Kanagal-Shamanna, Rashmi; Hill, Holly A; Yao, Yixin; Hagemeister, Fredrick B; Westin, Jason R; et al.
Summary: Background: Induction with ibrutinib and rituximab provides an opportunity to minimise chemotherapy exposure, because upfront use of these targeted therapies could result in remission without chemotherapy and allow for consolidation with only four cycles of chemotherapy instead of the conventional eight. We aimed to determine the activity and safety of ibrutinib–rituximab induction followed by shortened chemoimmunotherapy (four cycles) with rituximab plus hyper-fractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (R-HCVAD) alternating with methotrexate–cytarabine in previously untreated patients with mantle cell lymphoma. Methods: We did a single-centre, single-arm, phase 2 trial in previously untreated patients with mantle cell lymphoma. Eligible patients were aged 65 years or younger and had serum bilirubin of less than 1·5 mg/dL, creatinine clearance of 30 mL/min or more, Eastern Cooperative Oncology Group performance status of 2 or less, and cardiac ejection fraction 50% or more by echocardiogram. Patients received 12 cycles of ibrutinib–rituximab induction (part A; oral ibrutinib 560 mg daily and intravenous rituximab 375 mg/m 2 weekly for the first 4 weeks and then on day 1 of cycles 3–12). As soon as patients had a complete response, four cycles of R-HCVAD alternating with methotrexate–cytarabine (part B) were administered. If they did not have a complete response or had a partial response, patients received two cycles of R-HCVAD alternating with methotrexate–cytarabine followed by reassessment, up to a total of eight cycles. Patients were taken off study if they had stable disease or progression during R-HCVAD. The primary outcome was the overall response rate after part A. The analyses were conducted on an intention-to-treat basis. This trial is registered with ClinicalTrials.gov, number NCT02427620 . Findings: 131 patients were enrolled between June 12, 2015, and Dec 6, 2018. The median age was 56 years (IQR 49–60). 58 (50%) of 117 patients had high Ki-67 (≥30%). 129 (98%, 95% CI 95–100) of 131 patients had an overall response in part A. The most common grade 3–4 adverse events were lymphocytopenia (19 [14%] of 131), skin rash (16 [12%]), thrombocytopenia (12 [9%]), infections (11 [8%]), and fatigue (ten [8%]) in part A and lymphocytopenia (96 [73%]), leukocytopenia (42 [32%]), thrombocytopenia (40 [30%]), and neutropenia (26 [20%]) in part B. There was one on-study death, which was not deemed to be treatment-related. Interpretation: Induction with ibrutinib–rituximab in the frontline treatment of young patients with mantle cell lymphoma is active and safe. This approach allowed minimisation of the number of chemotherapy cycles, thereby reducing the adverse events associated with chemotherapy. Newer trials bringing the next-generation Bruton's tyrosine kinase inhibitors into the frontline setting might obviate the need for chemotherapy altogether in patients with mantle cell lymphoma. Funding: Pharmacyclics, Janssen.